A reversible high capacity data hiding scheme using combinatorial strategy. (2018) - Kumar, Rajeev; Chand, Satish; Singh, Samayveer
In this paper, we propose a new reversible high capacity data hiding scheme using combinatorial strategy which has very less distortion while hiding the secret data. It first builds a location map for the pixels of the cover image and then identifies the embeddable pixels. It divides the image into pairs of embeddable pixels and hides the secret data bits in each pair. The values of the embeddable pixels are updated according to pre-specified rules. The pixel values get changed at most by one and some of them may remain unchanged. Thus, there are minor changes in pixel values, which helps our scheme to achieve very good quality and with good hiding capacity. Furthermore, it is very simple as it just increases or decreases the pixel values rather than performing complex computations. The experimental results show that our scheme is superior to the state of the art schemes.